Structural Elucidation and Antibacterial Studies on Half-Sandwich Ruthenium(II) Complexes Incorporating Arene, Phosphine, Arsine and Thioamide Ligands - Pandey, R.N.; Gautam, K.V. (Asian Journal of Chemistry, 2015)
The half-sandwich arene complexes of ruthenium(II) incorporating arsine, phosphine and thioamide ligands with formula [Ru(h6-arene)(ER3)(AEtT)]+BPh4– h6-arene = C6H6 or p-cymene; E = P/As; R = C6H5/C6H5CH2; AEtT = 4-amino-3-ethyl-5-mercapto-1,2,4-triazole bidentate mononegative anion) are prepared and investigated. The reaction products have been characterized by elemental analyses, conductometric, magnetic, IR, UV-visible and 1H NMR spectra. Antibacterial activities of ligand and complexes are tested against E. coli, B. subtilus and S. aureus. The data revealed that all the complexes are more active than free thioamide ligand.